1996
DOI: 10.1038/bjc.1996.234
|View full text |Cite
|
Sign up to set email alerts
|

Clinical impact of detection of loss of heterozygosity of BRCA1 and BRCA2 markers in sporadic breast cancer

Abstract: Summary The development of familial and sporadic breast cancer is based on genetic alterations of tumoursuppressor genes, for which loss of heterozygosity (LOH) is one mechanism of gene inactivation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
52
4
2

Year Published

1996
1996
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(67 citation statements)
references
References 22 publications
9
52
4
2
Order By: Relevance
“…Although no link was found between the percentage of LOH at BRCA2 and Scarff-Bloom-Richardson (SBR) histopathological grade (P = 0.42), there was a correlation with the mitotic index, which is one of the three components of the SBR classification (P = 0.017). This was in partial agreement with previous reports of a link between LOH at BRCA2 and SBR histopathological grade III (Beckmann et al, 1996;Kelsell et al, 1996). Univariate analysis of MFS and S (log-rank test) showed no link with BRCA2 status (P = 0.34, P = 0.29 respectively).…”
supporting
confidence: 91%
See 2 more Smart Citations
“…Although no link was found between the percentage of LOH at BRCA2 and Scarff-Bloom-Richardson (SBR) histopathological grade (P = 0.42), there was a correlation with the mitotic index, which is one of the three components of the SBR classification (P = 0.017). This was in partial agreement with previous reports of a link between LOH at BRCA2 and SBR histopathological grade III (Beckmann et al, 1996;Kelsell et al, 1996). Univariate analysis of MFS and S (log-rank test) showed no link with BRCA2 status (P = 0.34, P = 0.29 respectively).…”
supporting
confidence: 91%
“…However, aberrant subcellular location (Chen et al, 1995) and reduced expression of BRCAJ (Thompson et al, 1995), together with high frequencies of loss of heterozygosity (LOH) on 17ql2-q21 and 13ql2-ql3 (sites of BRCAI and BRCA2) (Bieche and Lidereau, 1995), point to a significant role of these two genes in the tumorigenesis of sporadic breast cancer, but through a mechanism other than structural mutation. LOH on 13ql2-ql3 occurs in 30-60% of somatic breast tumours (Cleton-Jansen et al, 1995;Kerangueven et al, 1995;Beckmann et al, 1996;Hamann et al, 1996;Kelsell et al, 1996). These (Bignon et al, 1995;Beckmann et al, 1996;Kelsell et al, 1996).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Only 1 of them (5.5%) showed LOH at the BRCA1 locus, which could be explained either by the presence of an undetected mutation in the gene or by the occurrence of spontaneous LOH for the BRCA1 gene in a case not associated with this gene. Our results suggest that, unlike the sporadic cases, in which the rate of LOH for the BRCA1 locus is at least 30%, 8,12,13,24,25 in the familial cases not associated with the BRCA genes, the occurrence of LOH was very uncommon, confirming the idea of different mechanisms of tumorigenesis.…”
Section: Discussionsupporting
confidence: 71%
“…It is well established that the frequency of loss of heterozygosity at the BRCA2 locus increases in histologic grade III tumors compared to grade I and II tumors. 30 Thus, if loss of heterozygosity plays an important role in the downregulation of BRCA2 mRNA levels, BRCA2 mRNA levels in histologic grade III tumors should be lower than those in grade I and II tumors. However, we found that BRCA2 mRNA levels in histologic grade III tumors were significantly higher than those in grade I and II tumors.…”
Section: Discussionmentioning
confidence: 99%